Áreas protegidas sob o viés da conservação transfronteiriça: proposição para o Pampa do Rio Grande do Sul e Uruguai - Silva, Franciele da (2019)
Considering the Pampa of Rio Grande do Sul as a study area, the main discussion of this research is the ways of thinking about the conservation of the Pampas biodiversity, reconciling it with its cultural and economic base, as well as dialoguing with its cross-border character . Initially, an analysis was made of the possibilities of typologies of Protected Areas, in a national and international scope, that dialogue with the proposed objective, as well as a spatialisation of the Protected Areas already existing in the Pampa gaucho, focusing on areas that demand protection and were not yet covered by conservation policies. Using the mapping of the priority areas for conservation of the Pampa and the remnants of native vegetation, three areas could be identified that could be the target of a proposed Protected Area, the region of the western border being the target of the proposal, in four municipalities: Alegrete, Quaraí, Rosário do Sul and Santana do Livramento. Once the area was chosen, the typology that best suited it: a Biosphere Reserve. In their definition, Biosphere Reserves are areas of terrestrial, coastal / marine ecosystems, or a combination of both, recognized internationally, through the UNESCO Man and Biosphere Program (MAB), United Nations Educational, Scientific and Cultural Organization, since 1976. Conceptually, Biosphere Reserves are sites designed to demonstrate approaches to conservation and sustainable development on a regional scale, as well as providing territorial management initiatives to harmonize the coexistence between man and his living space. The main purpose of these Reserves is to protect biological diversity in strategic bioregions of the planet, reconciling conservation with development, and promoting scientific knowledge on these areas. Through this possibility, the research was structured, and a proposal for a Biosphere Reserve for the Pampa of Rio Grande do Sul was developed, adapting the guidelines proposed by UNESCO to the reality of the study area. The territorial limits of the Protected Area, their zoning and a plan of action were suggested. After elaboration of the proposal for the Pampa of Rio Grande do Sul, some points were discussed that could structure an integration between Brazil and Uruguay, culminating in the proposed research objective